Effects of systemic corticosteroids on blood eosinophil counts in asthma: real-world data. (3rd August 2019) - Ortega, Hector; Llanos, Jean-Pierre; Lafeuille, Marie-Helene; Duh, Mei Sheng; Germain, Guillaume; Lejeune, Dominique; Sama, Susan; Bell, Chris; Hahn, Beth
Abstract: Introduction : Systemic corticosteroids (SCS) are effective anti-inflammatory therapies for patients with severe or persistent asthma. Use of SCS reduces blood eosinophil counts; the magnitude and duration of reduction in real-world settings needs further investigation. Objective : To examine the SCS effect on blood eosinophil counts over time among patients with asthma in a real-world setting. Methods : This retrospective study used Reliant Medical Group (Worcester, MA) electronic medical records between January 2011 and December 2015. Patients aged ≥12 years with ≥1 SCS prescription (first: index date), ≥1 asthma diagnosis, and ≥1 eosinophil count in each 12-month pre- and post-index periods were included for the study. Endpoints included SCS treatment patterns, time to SCS discontinuation, and changes in index blood eosinophil counts (≥150, ≥300, and ≥400 cells/µL) with SCS initiation and discontinuation. Results : At index visit, 642 of 1198 included patients had a blood eosinophil count ≥150 cells/µL. After an average initial SCS prescription of 35 mg/day, mean (% change) eosinophil counts at month 1 in the ≥150, ≥300, and≥400 cells/µL subgroups decreased from index by 112 (−30%), 202 (−34%), and 290 (−36%) cells/µL, respectively. Of the patients with an eosinophil count ≥150 cells/µL at index, who discontinued SCS within 7, 14, or 21 days after the index date, 21%, 26%, and 25% had an eosinophil count <150 cells/µL 1-month post-index, respectively. Conclusion : Blood eosinophil counts decreased following initiation of SCS therapy and had not returned to index levels several weeks after SCS discontinuation. The time frame of SCS discontinuation is an important consideration when identifying patients with eosinophilic asthma.